Eirene-Sophia Kiapidou, Byzantine Historiographical Prefaces (4th–15th Centuries): A Study on the Praxis and Culture of Writing History in B yzantium (Byzantioς: Studies in Byzantine History and Civilization 23), Turnhout 2025 - ΛΑΜΠΑΚΗΣ Στυλιανός (Byzantina Symmeikta, 2025)
Eirene-Sophia Kiapidou, Byzantine Historiographical Prefaces (4th–15th Centuries): A Study on the Praxis and Culture of Writing History in Byzantium (Byzantioς: Studies in Byzantine History and Civilization 23), Turnhout 2025.